1981
DOI: 10.1115/1.3244527
|View full text |Cite
|
Sign up to set email alerts
|

Steam Condensation on Various Gold Surfaces

Abstract: Gold surfaces were investigated as promoters of dropwise condensation (DWC) of steam at atmospheric pressure. Very high heat fluxes at low ΔT’s may be achieved in this manner. Seven gold electroplating baths, one electroless immersion gold bath, and vacuum vapor deposition of gold were used. Five surface preparations for pure gold were tested. Gold deposits ranged in thickness up to 20,000 A.U. Auger electron spectroscopy and scanning electron microscopy were used to describe the surfaces chemically and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…It gives the atomic analysis of a surface, but unfortunately does not identify compounds. The technique was used in conjunction with the heat transfer tests described in this article (27). Carbon, undoubtedly present as organic compounds, was detected on every surface which produced dropwise condensation.…”
Section: Condensation On Solid Goldmentioning
confidence: 99%
See 1 more Smart Citation
“…It gives the atomic analysis of a surface, but unfortunately does not identify compounds. The technique was used in conjunction with the heat transfer tests described in this article (27). Carbon, undoubtedly present as organic compounds, was detected on every surface which produced dropwise condensation.…”
Section: Condensation On Solid Goldmentioning
confidence: 99%
“…A study of the minimum gold requirement to obtain dropwise condensation was carried out (27) varying the electroplating process. Brief consideration was also given to electroless immersion deposition and to vacuum deposition of gold on topper.…”
Section: Gold Bull 1981 14 (3)mentioning
confidence: 99%
“…However, it can be shown that the following relation approximates Eq. (4) to a high degree of accuracy (to within less than 0.5%).…”
Section: -1 Homogeneous Droplet Nucleationmentioning
confidence: 99%
“…Dropwise condensation is senerally the preferred mode of condensation because the resulting heat transfer coefficient may be as much as an order of magnitude higher than that for film condensation under comparable circumstances. Recent studies by Westwater and co-workers [4,5] have demonstrated that dropwise condensation of steam can be consistently obtained on gold and silver surfaces. The occurrence of dropwise condensation on gold and silver surfaces would appear to contradict the reasoning that high-surface-energy metal surfaces should be well wetted by the liquid phase, producing film condensation instead of dropwise condensation.…”
Section: -3 Dropwise Condensationmentioning
confidence: 99%
See 1 more Smart Citation